Intraductal Papillary Mucinous Neoplasia of the Pancreas - Pathologic Features and Molecular Markers - A Review - Cipriano, Maria Augusta (2019)
Intraductal papillary mucinous neoplasm (IPMN) of the pancreas are pre neoplastic lesions defined by the World Health Organization as a grossly visible intraductal epithelial neoplasm that arises in the pancreatic ductal system, composed of mucin producing cells. The predisposing factor for their development as well as genetics are still largely unknown. Pathologists have a pivotal role in IPMN management since features like IPMN subtype, degree of atypia, margins status and presence or absence of an invasive component imply different patient management. In this article, we perform a review of the pathological features and molecular markers of IPMNs.